Structural steel design to BS 5950 part 1 - Joannides, Frixos (Thomas Telford, 2002)
BS5950 - the design code for structural steel - has been greatly revised. Joannides and Weller introduce the new code and provide the necessary information for design engineers to implement the code when designing steel structures in the UK.